The swine acute diarrhea syndrome coronavirus spike protein promotes syncytial formation via upregulation of cellular cholesterol synthesis - Dakai Liu; Miaomiao Zeng; Jiyu Zhang; Liaoyuan Zhang; Hongyan Shi; Xin Zhang; Jialin Zhang; Jianfei Chen; Zhaoyang Ji; Xiuwen Li; Gengting Gu; Tingshuai Feng; et al. (mBio)
ABSTRACT Swine acute diarrhea syndrome coronavirus (SADS-CoV) is a novel coronavirus that causes acute diarrhea, vomiting, and high mortality in suckling piglets. Research has demonstrated that certain viruses enhance their replication by modulating intracellular cholesterol metabolism. However, the impact of SADS-CoV infection on cellular cholesterol synthesis remains unclear. Here, we found that SADS-CoV Spike (S) protein promoted syncytium formation by positively regulating cholesterol synthesis. Specifically, the virus upregulated the rate-limiting enzyme 3-hydroxy-3-methyl-glutaryl-CoA reductase through the inhibition of AMP-activated protein kinase (AMPK) activity. This inhibition was mediated by the activation of AKT-dependent phosphorylation of AMPKα at Ser485. Further investigation revealed that SADS-CoV S protein activated the PI3K/AKT pathway to promote cholesterol synthesis, a process that required the membrane protein integrin β1 (ITGB1). Importantly, we discovered that cholesterol facilitated cell-to-cell fusion mediated by the viral S protein, which enhanced syncytium formation. In summary, our findings demonstrate that the SADS-CoV S protein enhances cellular cholesterol accumulation by activating the PI3K/AKT/AMPK pathway through ITGB1, and that cholesterol facilitates syncytium formation mediated by the viral S protein. These insights contribute to a better understanding of SADS-CoV infection mechanisms and may inform future therapeutic strategies.IMPORTANCECholesterol, a vital component of cellular membranes, is crucial for maintaining cell structure and function. It also acts as an essential host factor for the entry, replication, and propagation of various viruses. In this study, we show that the Spike protein of swine acute diarrhea syndrome coronavirus (SADS-CoV) promotes syncytial formation by upregulating cellular cholesterol synthesis. The viral Spike protein activates the PI3K/AKT signaling pathway, leading to increased cholesterol production through the inhibition of AMP-activated protein kinase (AMPK). This upregulation of cholesterol facilitates cell-to-cell fusion, a process that enhances viral spread and pathogenesis. Moreover, we demonstrate that integrin β1 (ITGB1) acts as a critical host factor that links the viral Spike protein to the activation of the PI3K/AKT pathway. ITGB1 interacts with the S protein, playing a pivotal role in viral replication and cholesterol synthesis regulation. Our findings highlight the critical role of cholesterol in SADS-CoV infection and provide a deeper understanding of the molecular mechanisms behind viral replication. This research opens up potential therapeutic strategies targeting cholesterol metabolism to mitigate the effects of SADS-CoV and similar viral infections.